Electrocardiogram in Bitches Submitted to Unilateral Total Mastectomy - Fuchs, Karen Suzane; Mondardo Cardoso, Helena; Tochetto, Ronise; Comassetto, Felipe; da Rosa, Luara; Freccia, Carina; Ditzel da Costa Regalin, Bruna; Pilati, Celso; Oleskovicz, Nilson (Acta Scientiae Veterinariae, 2019)
Background: The frequency of oncological diseases in companion animals has increased in recent years, mainly due to the longer longevity of dogs. The neoplasms are not only open by the presence of the tumor and its location, but also by paraneoplastic syndromes, which are disorders that occur due to the production of substances by the tumor that cause. In addition to causing local changes and damages, oncological diseases may also result in injuries at distant sites, such as paraneoplastic syndromes, which, if untreated, may result in death of animals. The present study aimed to investigate whether female dogs with mammary tumors demonstrate electrocardiographic changes, and if so, to investigate whether these cease after removal of the tumor, and to relate the type of tumor with the occurrence of arrhythmias. Materials, Methods & Results: Eighteen female dogs, aged between 4 and 14 years, underwent electrocardiogram 24 h prior to undergoing a total unilateral mastectomy. After removal of the tumor, electrocardiograms were again performed 24 (M24), 48 (M48), and 72 (M72), as well as 14 days (M14d) after surgery. Histological analysis of the neoplasms showed that 55% of the tumors were benign, with predominance of adenoma (38%), and 45% were malignant, with predominance of adenocarcinoma (22%). The following rhythms and arrhythmias were observed: normal sinus rhythm (37.2%), sinus arrhythmia (62.8%), wandering pacemaker (26%), 1st degree atrioventricular block (AVB; 5%), premature ventricular complex (PVC; 10%), and T-wave > 25% of R-wave (25%); more than one change could occur simultaneously. Out of the evaluated electrocardiographic parameters, a significant difference was observed in the QT interval between the following timepoints: M24 (204 ± 18), M48 (204 ± 22), and M72 (203 ± 23), as well as Mbasal (192 ± 15) and M14d (178 ± 43). Discussion: Regarding the observed rhythms, arrhythmias, and changes, respiratory sinus arrhythmia was the normal predominant rhythm, followed by sinus rhythm. Wandering pacemaker in conjunction with respiratory sinus arrhythmia is widely observed in dogs; these conditions occur due to vagal predominance, without hemodynamic consequences. PVC is the premature depolarization originating in ectopic foci of the ventricular tissue, and is considered the most common type of ventricular arrhythmia in small animals. Two animals demonstrated PVC, one in Mbasal and the other in M14d. The former presented with a tumor diagnosed as an adenocarcinoma, which could be related to the paraneoplastic syndrome. The later presented with a tumor diagnosed as an adenoma, indicating that PVC may have occurred due to stress at that time. The T-wave occurs after ventricular depolarization, and is usually up to 25% of the amplitude of the R-wave. This change was observed at all times for the animal that was histologically diagnosed as having mammary adenocarcinoma, and may have been related to the neoplasm or be an individual change. The 1st degree AVB occurred in Mbasal, and was therefore related to increased vagal tonus. The significant differences in the QT interval were negatively correlated with decreased heart rate (HR), i.e., the QT interval increased when HR decreased. This must have been related to the acclimatization of the animals to the tests. Owing to the high number of animals with early-stage mammary tumors in this study, the observed electrocardiographic changes could not be correlated with tumor presence and type.